Manajemen Pengembangan Kompetensi Guru Pendidikan Agama Buddha Berbasis Kepemimpinan Spiritual : Systematic Literature Review (SLR) - Novita Novita; Budi Utomo; Riasih Riasih; Leon Leon (Journal of Literature Review, 2026)
Teacher competency development is a strategic factor in improving educational quality, particularly in Buddhist religious education, which emphasizes the integration of professional competence and spiritual values. However, studies addressing competency development management strategies based on spiritual leadership in Buddhist education remain limited. This study aims to analyze strategic approaches to managing the competency development of Buddhist religious education teachers through the lens of spiritual leadership by synthesizing previous research findings. The study employed a Systematic Literature Review (SLR) with a descriptive qualitative approach. The literature search involved query transformation, predefined inclusion and exclusion criteria, and backward and forward citation tracking, resulting in 50 eligible articles for analysis. The findings indicate that the most prominent dimensions of spiritual leadership include vision, hope/faith, altruistic love, spiritual role modeling, and the internalization of Buddhist values. Teacher competency development primarily emphasizes professional and pedagogical competencies, which contribute to improved teacher performance, organizational culture, work motivation, and instructional quality. Most studies were conducted in formal educational settings, whereas research specifically addressing Buddhist religious education remains limited. This study concludes that integrating spiritual leadership theory with Buddhist principles, including sīla (morality), samādhi (concentration), and paññā (wisdom), provides a holistic, sustainable, and contextually relevant management strategy for enhancing teacher competency in Buddhist educational institutions.